FEA and Structural Optimization of the Planet Carrier of the Speed-increase Gearbox - Pan Jinkun; Geng Feng (Jixie chuandong)
On the purpose of lightweight design,on the condition that it meets the strength and stiffness requirements the designer began to structural optimization of the planet carrier of speed-increase gearbox.First,the analysis of the strength and stiffness of planet carrier is carried out,and then the structure size which posts an important impact on planet carrier is decided as the design variable.Second,using high-end mesh morph software,the parameterized model of grid is established,and then go further,the optimized model of planet carrier on the purpose of decreasing its weight is built.Finally,the optimized analysis is carried out in combination of Isight multidisciplinary optimization software,the reasonable design plan for lightweight of planet carrier is obtained.The modal analysis towards the optimized planet carrier is carried out,and its natural frequency completely avoid meshing frequency,so as to avoid resonance phenomenon.